(untitled) (diségno, 2020)
The essay critically investigates some drawings elaborated by Giovanni Battista Cipriani during his architectural studies with Giuseppe Palazzi, in the 1780s in Rome. Relationships between these drawings and their known graphic sources are studied and can be traced back to some plates of the first Libro primo Scielta di varii tempietti antichi di Giovanni Battista Montano (Rome 1624) in the edition of 1684. These drawings have a double meaning for the history of Representation, as they are the results of an eidetic practice that acts an interpretative process of a given graphic source – which has become a building on paper to be surveyed and synthetically redrawn – or as the final result of a process of partial reconfiguration with heuristic values, at least as regards the use of drawing as a tool for representing architect’s ideas and projects. From this point of view, Cipriani’s works become interpreting tools for the practice of surveying drawing and graphic sources, as well as symbols of the value of drawing intended as an expression of the memory of its author, as it happened when re-annotated on the Libraccio o miscellanea di memorie spettanti alle belle arti (1801 e seg.), the model of the ‘opera omnia’ representing Cipriani’s concept of eidetic knowledge.